2009
DOI: 10.1017/s1368980009005205
|View full text |Cite
|
Sign up to set email alerts
|

Maternal iodine status and neonatal thyroid-stimulating hormone concentration: a community survey in Songkhla, southern Thailand

Abstract: Objective: To determine iodine intake and urinary iodine excretion (UIE) in a group of pregnant Thai women and the concentration of thyroid-stimulating hormone (TSH) in their neonates. Design: A prospective cohort study. Setting: Three districts of Songkhla, southern Thailand. Subjects: Two hundred and thirty-six pregnant women. Results: A quarter of the participants lacked knowledge of iodine and the prevention of iodine deficiency, although 70 % used iodized salt. Those who did not use iodized salt stated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 10 publications
2
17
1
3
Order By: Relevance
“…In this study only 50% of the study population who have a weight gain within the accepted range 11-16 kg) had given birth to infants whose birth weight was within the normal range (2500≤3500) (9). Only 30% of the study sample having a good knowledge on nutrition has given birth to infants whose birth weight was within the accepted range (2500≤3500 kg) although no significant difference was observed between knowledge on nutrition & infant birth weight in the present study.…”
contrasting
confidence: 64%
“…In this study only 50% of the study population who have a weight gain within the accepted range 11-16 kg) had given birth to infants whose birth weight was within the normal range (2500≤3500) (9). Only 30% of the study sample having a good knowledge on nutrition has given birth to infants whose birth weight was within the accepted range (2500≤3500 kg) although no significant difference was observed between knowledge on nutrition & infant birth weight in the present study.…”
contrasting
confidence: 64%
“…Some experts have proposed that the data on neonatal TSH screening for monitoring population iodine deficiency should be interpreted with caution due to technical issues including the time of sampling after birth (38). Nevertheless, many studies have shown an inverse relationship between neonatal TSH and maternal urinary iodine concentration, supporting the notion that the frequency of neonatal TSH concentrations >5 µU/mL was a sensitive indicator of iodine nutrition during pregnancy (39,40,41). In recent years, several studies have already demonstrated insufficient iodine intake of pregnant women living in different regions of Turkey (17,18), including apparently iodine-sufficient areas (19).…”
Section: Discussionmentioning
confidence: 84%
“…However, a proper balance of iodine intake is needed during pregnancy for the mother and the developing fetus. Studies have demonstrated that iodine deficiency during pregnancy may lead to maternal hypothyroidism (13) and impaired physical and intellectual development (14). Thus, many countries and institutions such as the World Health Organization (WHO) and the Food and Agriculture Organization (FAO) have established that the recommended nutrient intake of iodine for pregnant women should be at least 250 g/d (6,15).…”
Section: Discussionmentioning
confidence: 99%
“…In Haixing, pregnant women had higher serum concentrations of sTSH (2.89 vs. 2.19 mIU/liter; Z ϭ3.283; P ϭ 0.001) and FT 3 (4.03 vs. 3.78 pmol/liter; t ϭ 3.572; P Ͻ 0.001), and lower concentrations of FT 4 (13.35 vs. 13.77 pmol/liter; t ϭ Ϫ2.048; P ϭ 0.041) than pregnant women from Tianjin (Table 2). There were no significant differences in the positive rates of TPOAb and TgAb in pregnant women between Haixing and Tianjin (16.2 vs. 24.1% for TPOAb and 7.1 vs. 3.4% for TgAb; P Ͼ 0.05; Table 2).…”
Section: Thyroid Hormones and Autoantibodiesmentioning
confidence: 99%